2008
DOI: 10.1016/j.jcrysgro.2007.12.010
|View full text |Cite
|
Sign up to set email alerts
|

In situ observation of composition profiles in the solution by X-ray penetration method

Abstract: The X-ray penetration intensity during the diffusion process of NH 4 Br into H 2 O was measured by a CdTe line sensor as a function of time and it was converted to the NH 4 Br composition using a calibration line. The diffusion coefficient of NH 4 Br into H 2 O was estimated to be 2.2 Â 10 À5 cm 2 /s by comparing the calculated results. The method was applied to the growth of InGaSb from the In-Ga-Sb solution. The indium composition profiles in the solution were measured and growth of InGaSb from the In-Ga-Sb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Rajesh et al 7) carried out an in-situ observation of In x Ga 1-x Sb crystal growth in a furnace with temperature gradient along the growth ampoule. In this experiment, a cartridge of GaSb/InSb/GaSb sandwich structure was used, and the dissolution process of GaSb was examined by the X-ray penetration method 6) . When the cartridge is heated over the melting point of InSb, the InSb-melt was established in the middle region because the melting point of InSb is lower than that of GaSb.…”
Section: Introductionmentioning
confidence: 99%
“…Rajesh et al 7) carried out an in-situ observation of In x Ga 1-x Sb crystal growth in a furnace with temperature gradient along the growth ampoule. In this experiment, a cartridge of GaSb/InSb/GaSb sandwich structure was used, and the dissolution process of GaSb was examined by the X-ray penetration method 6) . When the cartridge is heated over the melting point of InSb, the InSb-melt was established in the middle region because the melting point of InSb is lower than that of GaSb.…”
Section: Introductionmentioning
confidence: 99%
“…Several numbers of reports are available in literature for the in-situ observation of growth process of Si [17][18][19][20][21] as well as various binary materials [22][23][24][25][26][27]. However, only very few works were reported on the in-situ observation [9,28] and numerical investigation [29,30] of high temperature growth process of ternary alloy semiconductor materials. When compared to binary materials, the dissolution process and growth kinetics are more complicated for ternary materials.…”
Section: Introductionmentioning
confidence: 99%
“…Due to fundamental as well as increasing technological importance of the III-V alloy semiconductors, it is indispensable to understand the growth kinetics of the material by means of insitu observations. In this point of view, Hayakawa et al [18] observed the diffusion process of NH 4 Br into H 2 O as a function of time by X-ray penetration method using a CdTe detector and the penetrated X-ray intensity was converted to the NH 4 Br composition using a calibration line. Based on the above method, indium composition profiles in the In-Ga-Sb solution were measured using the cylindrical shaped GaSb/InSb/GaSb sandwich sample [18].…”
Section: Introductionmentioning
confidence: 99%
“…In this point of view, Hayakawa et al [18] observed the diffusion process of NH 4 Br into H 2 O as a function of time by X-ray penetration method using a CdTe detector and the penetrated X-ray intensity was converted to the NH 4 Br composition using a calibration line. Based on the above method, indium composition profiles in the In-Ga-Sb solution were measured using the cylindrical shaped GaSb/InSb/GaSb sandwich sample [18]. In addition, they have investigated the growth rate and the solid-liquid interface shape of the In x Ga 1 À x Sb crystals using the heat pulse technique and numerical simulation [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%